2013
DOI: 10.1161/atvbaha.113.301290
|View full text |Cite
|
Sign up to set email alerts
|

Photodynamic Therapy Using a Protease-Mediated Theranostic Agent Reduces Cathepsin-B Activity in Mouse Atheromata In Vivo

Abstract: M atrix-disorganizing proteases, such as cathepsins or matrix metalloproteinases from macrophages, can destabilize atheromata, followed by plaque rupture to cause thromboembolic stroke or myocardial infarction. [1][2][3][4] We previously showed that molecular imaging of cathepsin-B (CatB) or matrix metalloproteinase-2/9 protease activity reflected the inflammatory component of atherosclerotic pathology in mice 5 and human atheromata. 6 We also showed that the protease imaging could quantitatively demonstrate p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
36
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 50 publications
(43 citation statements)
references
References 21 publications
2
36
0
Order By: Relevance
“…Therefore, it can serve as both a stimulus and a target for drug delivery in atherosclerosis management. Shon et al developed protease‐mediated theranostic agents (L‐SR15 agents) for PDT that could suppress cathepsin B activity. L‐SR15 activation was mediated by cathepsin Bs that released Ce6 molecules leading to the reduction of foam cells via PDT .…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it can serve as both a stimulus and a target for drug delivery in atherosclerosis management. Shon et al developed protease‐mediated theranostic agents (L‐SR15 agents) for PDT that could suppress cathepsin B activity. L‐SR15 activation was mediated by cathepsin Bs that released Ce6 molecules leading to the reduction of foam cells via PDT .…”
Section: Applicationsmentioning
confidence: 99%
“…To date, multi‐stimuli‐responsive AND‐based nanosystems have shown great promise in enhancing drug delivery efficiency to atherosclerotic lesions. Shon et al, for instance, have developed dual‐responsive theranostic nanoagents (L‐SR15 agents) that were active in response to light and enzyme (cathepsin B) stimuli. Without the presence of cathepsin Bs, the L‐SR15 nanoagents were still inactive.…”
Section: Applicationsmentioning
confidence: 99%
“…Maiseyeu et al 156 showed that gadolinium nanoparticles conjugated with a neutralizing antibody against myeloid-related protein (Mrp)-8/14 (a secreted protein previously shown to promote leukocyte recruitment) limit Mrp-8/14-dependent inflammatory activation of bone marrow-derived macrophages in vitro and selectively image at CONS CALIFORNIA DIG LIB on November 19, 2014 http://atvb.ahajournals.org/ Downloaded from inflammatory cells in lesions of Apoe −/− mice, suggesting a potential theranostic approach for atherosclerosis. Others have developed photodynamic therapy to image and kill activated and detrimental macrophages within atherosclerotic lesions, 157 using a combination of photosensitizers and light illumination. In particular, the authors developed a cathepsin B-activatable theranostic agent, which becomes fluorescent and generates singlet oxygen on protease conversion followed by light therapy.…”
Section: Monocytes/macrophages As Therapeutic Targetsmentioning
confidence: 99%
“…They showed selective imaging of macrophage-dependent cathepsin B activity in lesions of Apoe −/− mice, followed by significant reduction of macrophage content after application of light therapy, mostly because of macrophage apoptosis. 157 Future work should define the use and potential undesirable effects of this attractive see-and-treat approach. Induction of massive macrophage apoptosis in advanced lesions might promote necrotic core formation in the absence of effective efferocytosis pathways.…”
Section: Monocytes/macrophages As Therapeutic Targetsmentioning
confidence: 99%
“…These activatable PDT agents were shown to be highly efficient in selectively killing target cancer cells while minimizing unwanted skin photosensitivity. Recently, we showed the first successful in vivo results demonstrating the potential utility of an enzyme-activatable PDT agent in near-infrared (NIR) fluorescence imaging and the subsequent PDT of atherosclerosis 31. The cathepsin B-activatable photodynamic theranostic agent reduced cathepsin-B activity in mouse atheromata and stabilized inflammatory plaques by selectively killing the activated macrophages in the diseased regions.…”
Section: Introductionmentioning
confidence: 99%